2015
DOI: 10.1016/j.jtbi.2014.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Osteocytes as a record of bone formation dynamics: A mathematical model of osteocyte generation in bone matrix

Abstract: The formation of new bone involves both the deposition of bone matrix, and the formation of a network of cells embedded within the bone matrix, called osteocytes. Osteocytes derive from bone-synthesising cells (osteoblasts) that become buried in bone matrix during bone deposition. The generation of osteocytes is a complex process that remains incompletely understood. Whilst osteoblast burial determines the density of osteocytes, the expanding network of osteocytes regulates in turn osteoblast activity and oste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 74 publications
0
64
0
Order By: Relevance
“…At this stage, imaging modalities in the hard tissue of bone have not yet allowed specific location of these interactions, exchange of soluble factors, or juxtacrine signalling specifically at the site of dendrite tip to tip contact. However, the efficiency of cell-contactdependent wire transmission through the dendritic network may also depend on absolute number of cells within the network given the possibility of distant neighbour connections and of direct connections to the vascular pore surface [22,49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At this stage, imaging modalities in the hard tissue of bone have not yet allowed specific location of these interactions, exchange of soluble factors, or juxtacrine signalling specifically at the site of dendrite tip to tip contact. However, the efficiency of cell-contactdependent wire transmission through the dendritic network may also depend on absolute number of cells within the network given the possibility of distant neighbour connections and of direct connections to the vascular pore surface [22,49].…”
Section: Discussionmentioning
confidence: 99%
“…This extensive level of replenishment suggests that therapeutic approaches that change the nature of new osteocytes being deposited (such as gene therapy approaches that target the osteoblast) may allow rapid incorporation of modified osteocytes within the skeleton. It also indicates that a large number of bone surface osteoblasts are incorporated into the matrix, in a manner dependent on signals from within the extensive osteocytic network [49]. Although these proportions are unclear, it has been suggested that 19-29% of the osteoblast population is incorporated into the bone matrix [25,28], suggesting that the number of osteoblasts produced per day in the skeleton ranges from 1.14 × 10 11 -1.7 × 10 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In bone remodeling, osteoclasts dissolve/resorb old bone tissue and osteoblasts produce osteocytes, actively renewing bone tissue. Bone tissue participates in numerous functions: it maintains blood pH levels, acts as calcium and phosphate storage, provides protection of vital organs and support for muscles, organs, and soft tissues, helps with leverage and movement, and, lastly, participates indirectly in the formation of blood cells in the bone marrow interspersed within the spongy bones [73].…”
Section: Bone Mass: Osteopenia and Osteoporosismentioning
confidence: 99%
“…The osteocyte lacunar density, evaluated by 2D analysis of qBEI, was increased by nearly 40%, which is possibly related to enhanced cell proliferation and/or altered cell differentiation, as observed in cell cultures from affected bone . It has been speculated indeed, that the quantity of osteocytes generated during bone formation depends, on the one hand, on the number of preexisting osteoblasts and, on the other hand, on their matrix synthesis activity . Thus, in melorheostotic bone, more osteocytes might be encased in the matrix because a larger osteoblastic pool is present and/or because less matrix is synthesized at the single‐cell level, which would be in line with a reduced COL1A1 expression observed in affected osteoblasts .…”
Section: Discussionmentioning
confidence: 96%